Notch 1 Is Involved in CD4+ T Cell Differentiation Into Th1 Subtype During Helicobacter pylori Infection - Xie, Jinling; Wen, Junjie; Chen, Chuxi; Luo, Meiqun; Hu, Bingxin; Wu, Danlin; Ye, Jianbin; Lin, Yanqing; Ning, Lijun; Ning, Yunshan; Li, Yan (Frontiers in Cellular and Infection Microbiology, 2020)
Helicobacter pylori (H. pylori) infection induces CD4+ T differentiation cells into IFN-γ-producing Th1 cells. However, the details of mechanism underlying this process remain unclear. Notch signal pathway has been reported to regulate the differentiation of CD4+ T cells into Th1 subtype in many Th1-mediated inflammatory disorders but not yet in H. pylori infection. In the present study, the mRNA expression pattern of CD4+ T cells in H. pylori-infected patients differed from that of healthy control using Human Signal Transduction Pathway Finder RT2 Profiler PCR Array and this alteration was associated with Notch signal pathway, as analyzed by Bioinformation. Quantitative real-time PCR showed that the mRNA expression of Notch1 and its target gene Hes-1 in CD4+ T cells of H. pylori-infected individuals increased compared with the healthy controls. Additionally, the mRNA expression of Th1 master transcription factor T-bet and Th1 signature cytokine IFN-γ was both up-regulated in H. pylori-infected individuals and positively correlated with Notch1 expression. The increased protein level of Notch1 and IFN- were also observed in H. pylori-infected individuals confirmed by flow cytometry and ELISA. In vitro, inhibition of Notch signaling decreased the mRNA expression of Notch1, Hes-1, T-bet and IFN-, and reduced the protein levels of Notch1 and IFN- and the secretion of IFN- in CD4+ T cells stimulated by H. pylori. Collectively, this is the first evidence that Notch1 is up-regulated and involved in the differentiation of Th1 cells during H. pylori infection, which will facilitate exploiting Notch1 as a therapeutic target for the control of H. pylori infection.